Silício na morfofisiologia de plantas de coquinho-azedo (Butia capitata) - Costa, Irton de Jesus Silva (2017)
Butia capitata (Mart.) Becc, also known by the names butiá, coco-cabeçudo, coquinho, butiá-dapraia and coco-babão, belongs to the family Arecaceae. This species has great economic potential because its fruits are widely used. The addition of silicon to the substrate may help to obtain more vigorous seedlings. Its use contributes to the final quality of the plants, as it provides accumulation in the leaves' cuticle allowing protection to the plants, increase of the photosynthetic capacity, reduction of water loss and also it improves growth. The objective of this study was to evaluate the effect of silicon on the growth, morphophysiology and its accumulation by coquinho-azedo plants. The design was a completely randomized in a double factorial scheme (5 x 5), with five concentrations and five evaluation periods, subdivided in time, with 8 plants / plot, totaling 400 plants. Ten replicates were used per treatment. The treatments consisted of five concentrations (0, 0.30, 0.60, 0.90 and 1.20 g / pot of silicon), in the form of 1% silica solution (SiO2.XH2O). This solution was applied around the drench strain, the pots that constituted the control received water in the same amount. Growth analysis, silicon concentration, flow, anatomical and ultrastructural cytometry, gas exchange, chlorophyll content, relative chlorophyll index, relative water content and electrolyte extravasation were performed. It is concluded that the use of silicon provides better growth of coquinho-azedo and its species is accumulator of silicon in the leaf and root. The DNA content is modified in coquinho-azedo plants at a concentration of 0.90 g / pot of silicon which changes foliar and root anatomy of Butia capitata. Silicon increases the photosynthetic and transpiratory rate. There is deposition of silicon on both sides of the leaves of this species. The concentration 0.60 g / pot of silicon provides higher levels of chlorophyll b and carotenoids. The concentrations 0.90 and 1.20 g / pot of silicon provide a higher chlorophyll a / b ratio. The concentration 0.60 g / pot of silicon provides greater relative water content in Butia capitata leaves.